MAKNA LIRIK LAGU “HATI-HATI DI JALAN” OLEH TULUS: KAJIAN SEMIOTIKA NARATIF - Rohma Tunurus Asholiha; Edi Dwi Riyanto (Haluan Sastra Budaya, 2023)
With the many social media platforms currently available, one of which is YouTube, encouraging the birth of so many audio-visual communications that can be uploaded for free by anyone, anytime and anywhere. This study discusses the analysis of the meaning of the lyrics of the song careful on the road by Tulus. The song Cautious on the Road was released on March 3, 2022. The theories used in this research are the Stuart Hall circuit of culture theory to get representation in society, and Michael Riffaterre's semiotic theory to explain the meaning in this song. The method used in this research is qualitative descriptive. The video clip and song lyrics convey a message about the meaning of being careful on the road, where the message is conveyed through the form of visualization shown in the music video and also through the song from the music video. This can be seen from the many positive responses through the comments column and also the number of impressions that made up 1 million people in less than 1 month.